2017
DOI: 10.1186/s12954-017-0156-z
|View full text |Cite
|
Sign up to set email alerts
|

Needle exchange programs for the prevention of hepatitis C virus infection in people who inject drugs: a systematic review with meta-analysis

Abstract: BackgroundPrevious research on the effectiveness of needle exchange programs (NEP) in preventing hepatitis C virus (HCV) in people who inject drugs (PWID) has shown mixed findings. The purpose of this study was to use the meta-analytic approach to examine the association between NEP use and HCV prevention in PWIDs.MethodsStudy inclusion criteria were (1) observational studies, (2) PWIDs, (3) NEP use, (4) HCV status ascertained by serological testing, (5) studies published in any language since January 1, 1989,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 55 publications
3
39
0
1
Order By: Relevance
“…It is important to remember that individual studies on this topic are retrospective in design because it would be an unethical violation of beneficence to randomize people away from the potentially beneficial intervention of NEPs. For this reason, they are frequently combined into meta‐analyses that show conflicting evidence on the impact of NEPs in reducing HCV transmission, particularly in North America . Many of the inconsistencies in the data can be explained by confounding, misclassification of the intervention exposure, and bias.…”
Section: Limitations Of Available Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to remember that individual studies on this topic are retrospective in design because it would be an unethical violation of beneficence to randomize people away from the potentially beneficial intervention of NEPs. For this reason, they are frequently combined into meta‐analyses that show conflicting evidence on the impact of NEPs in reducing HCV transmission, particularly in North America . Many of the inconsistencies in the data can be explained by confounding, misclassification of the intervention exposure, and bias.…”
Section: Limitations Of Available Datamentioning
confidence: 99%
“…Confounding exists because of inadequate control for important covariables influencing HCV transmission, such as frequency of injection, duration and type of injection drug use, baseline injection risk behavior, homelessness, and high‐risk sexual practices. In one meta‐analysis, only half of the studies controlled for any confounders in their data . Misclassification of the intervention exposure has also been widespread, with many studies failing to standardize for the intervention of interest: high‐coverage NEPs.…”
Section: Limitations Of Available Datamentioning
confidence: 99%
See 1 more Smart Citation
“…NSP is recommended to reduce the spread of HIV and hepatitis in PWID . Certain reviews have concluded that there is evidence that NSP is reducing injection risk behaviour and transmission of HIV but the data are insufficient to confirm its effectiveness in preventing the transmission of HCV . On the other hand, there are studies showing that NSP prevents HCV transmission, in particular when it is combined with OAT .…”
Section: Harm Reduction Measuresmentioning
confidence: 99%
“…16,[33][34][35] Certain reviews have concluded that there is evidence that NSP is reducing injection risk behaviour and transmission of HIV but the data are insufficient to confirm its effectiveness in preventing the transmission of HCV. [36][37][38] On the other hand, there are studies showing that NSP prevents HCV transmission, in particular when it is combined with OAT. 16,35 In a recent Cochrane report, Platt et al concluded that OAT was associated with a 50% reduction in the HCV transmission rate, while needle exchange programs (NEP) alone was less effective with a reduction of 21%.…”
Section: Harm Reduc Tion Me a Sure Smentioning
confidence: 99%